V.1 - India Planning Commission (New Delhi, 2008)
Part I of this two volume set explains the processes and procedures of economic planning in India, focusing on institutional framework, mechanism of transferring resources from the Center to the States for plan purposes, objectives of planning, and an assessment of achievements. Parts II to XIII of the book contain edited extracts from Final Plan Documents from the First Five Year Plan (1951-52 to 1955-56) to the Eleventh Five Year Plan (2007-08 to 2011-12). These have been categorized into the following twelve themed headings, covering almost all the sectors of the Indian economy: Agriculture, Land Reforms, Co-operatives and Allied Sectors . Industry, Infrastructure, Public Sector and Small Industries . Development and Management of Extractive Industries (Mineral Resources) . Electricity, Coal, Petroleum and Other Energy Sources . Urban Development and Housing . Transport and Communications . Employment and Labour Welfare . Health and Family Welfare . Education and Training . Science and Technology . Social Welfare . Development of North Eastern States, Hill Areas, Tribal Areas and Other Measures for Balanced Regional Development. Editorial comments are given at the beginning of each theme heading, providing easy comprehension on how a particular sector of the Indian economy was treated in terms of priority, strategy, and allocation of resources in the successive Plans. Part XIV contains sector-wise statistical data on the Indian economy (1950-51 to 2006-07) which will be useful for a cross-section of academic researchers, both in India and abroad. This work will prove useful for scholars of economics, commerce, public administration, and business management. An understanding of the mechanics of economic planning will also serve the needs of legislators, administrators, and those in industry and trade.
Keywords: Planning - India